A high heat-resistant aluminum-based copper-clad laminate and preparation method thereof
By using silicone elastomer and MQ silicone resin-enhanced epoxy resin in the insulating adhesive layer of aluminum-based copper clad plate, the problem of insufficient heat resistance, toughness and bond strength of the insulating adhesive layer in the prior art is solved. Higher heat resistance and toughness are achieved while maintaining good bonding properties.
Patent Information
- Application Number
- CN202410201418.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-19
- Filing Date
- 2024-02-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-02-23
AI Technical Summary
The insulating adhesive layer of the existing aluminum-based copper clad plate has problems of insufficient heat resistance, toughness and bonding strength, resulting in a degradation of performance under high temperature and long-term aging conditions.
A high-performance insulating adhesive layer is formed by a specific preparation method using silicone elastomer and MQ silicone-reinforced epoxy resin as components of the insulating adhesive layer.
The heat resistance, insulation, toughness and bonding strength of aluminum-based copper clad plate are significantly improved, and its performance stability under high temperature and long-term use conditions are enhanced.
Smart Images

Figure BDA0004711577740000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PCB materials and functional adhesives, and specifically relates to a high-heat-resistant aluminum-based copper-clad laminate and a preparation method thereof. Background Art
[0002] Aluminum-based copper-clad laminate is a plate-shaped material made of electronic glass fiber cloth or other reinforcing materials impregnated with resin, single resin, etc. as an insulating adhesive layer, covered with copper foil on one or both sides and hot-pressed. As a substrate material in the manufacture of printed circuit boards, aluminum-based copper-clad laminates mainly play the role of interconnection, insulation and support for printed circuit boards, and have a great influence on the transmission speed, energy loss and characteristic impedance of signals in the circuit. The performance, quality, processability, manufacturing level, manufacturing cost, long-term reliability and stability of printed circuit boards depend to a large extent on aluminum-based copper-clad laminates.
[0003] At present, the single resin insulating adhesive layer in aluminum-based copper-clad laminates mainly uses epoxy resin as the bonding body, which is combined with a curing agent and a thermal conductive filler and then hot-pressed and formed after curing or without curing. However, pure epoxy resin has the defects of poor heat resistance and poor toughness. The above defects can be improved by designing the adhesive composition.
[0004] For example, patent CN 102746615 B discloses a high heat-resistant, high insulation and thermally conductive aluminum-based copper-clad laminate formulation and preparation process, which improves toughness by adding terminal hydroxyl polybutadiene liquid rubber to the composite epoxy resin, uses specific benzyldimethylamine, dinitrile amine crosslinking agent and KH-560 silane coupling agent to improve bonding strength, and uses specific boron nitride powder, aluminum oxide powder, aluminum nitride powder and silicon nitride powder as fillers to enhance thermal conductivity. However, the above-mentioned bonding components are relatively complex, and the quality index control of raw materials is relatively strict in the actual production process, and the production stability is poor. Patent CN 106467668 B discloses a silicone resin aluminum-based copper-clad laminate, whose insulating adhesive layer is prepared from a silicone resin composition, and the silicone resin composition is obtained by catalytic reaction using methyl vinyl silicone resin or / and methylphenyl vinyl silicone resin under the conditions of terminal vinyl silicone oil as an active diluent and hydrogen-containing silicone oil crosslinking agent. Excellent electrical insulation performance, thermal conductivity, high temperature resistance and long-term aging resistance can be achieved. However, the surface tension of a simple silicone resin composition is relatively low, resulting in low bonding strength to the aluminum plate and copper foil, and the resulting aluminum-based copper-clad laminate is at risk of debonding and cracking.
[0005] Therefore, if an insulating adhesive layer component can be developed that can achieve good high temperature resistance, electrical insulation performance, and good bonding strength and toughness, it will have significant practical significance and commercial value for the production of high-quality aluminum-based copper clad laminates. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a highly heat-resistant aluminum-based copper-clad laminate. The aluminum-based copper-clad laminate of the present invention uses an organic silicone elastomer and an epoxy resin reinforced with MQ silicone resin as an insulating adhesive layer between the aluminum plate layer and the copper foil layer, which can significantly improve the heat resistance, insulation, toughness and strength of the aluminum-based copper-clad laminate.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned high heat-resistant aluminum-based copper-clad laminate.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A high heat-resistant aluminum-based copper-clad laminate comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight:
[0010]
[0011] The silicone elastomer reinforcing agent is prepared by the following method:
[0012] (1) adding a side chain hydrogen-containing polysiloxane and an allyl polyoxyethylene ether to an organic solvent and stirring to dissolve them uniformly, then adding a platinum complex catalyst, heating and stirring under an inert atmosphere to react until the alkenyl reaction is complete, thereby obtaining a polyether grafted polysiloxane solution;
[0013] (2) adding diisocyanate to the obtained polyether grafted polysiloxane solution to carry out a cross-linking reaction, and after the reaction is completed, removing the organic solvent by distillation under reduced pressure to obtain a silicone elastomer reinforcing agent.
[0014] In the preparation of the above-mentioned silicone elastomer reinforcing agent, the weight average molecular weight of the side chain hydrogen-containing polysiloxane is 2000-15000 g / mol, and the active hydrogen content (mass percentage) is 0.2%-0.8%. Side chain hydrogen-containing polysiloxane is a common chemical raw material, and its molecular formula is SiO(CH3)3[SiO(CH3)(H)] m [SiO(CH3)2] n Si(CH3)3.
[0015] The weight average molecular weight of the allyl polyoxyethylene ether is preferably 1000 to 2400 g / mol. Allyl polyoxyethylene ether is a commonly used chemical raw material, and its molecular formula is CH2=CHCH2O(C2H4O) n H. It is found in the present application that too low molecular weight of allyl polyoxyethylene ether will lead to a significant reduction in heat resistance and toughening effect. The reason may be that the compatibility of the polysiloxane grafted with lower molecular weight allyl polyoxyethylene ether and the epoxy resin matrix is poor, resulting in a reduction in the improvement effect.
[0016] Preferably, the molar ratio of the allyl polyoxyethylene ether to the active hydrogen content in the side chain hydrogen-containing polysiloxane is 0.7 to 1:1.
[0017] The organic solvent in step (1) can be N-methylpyrrolidone or N,N-dimethylformamide. The above solvent has good solubility and has a good promoting catalytic effect on the subsequent diisocyanate cross-linking reaction.
[0018] The temperature of the heating and stirring reaction in step (1) is 60-90°C.
[0019] The diisocyanate in step (2) can be selected from at least one of toluene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate. The above diisocyanate has good cross-linking activity for polyether-grafted polysiloxane, cross-linking the polysiloxane to form an elastomeric structure, and has a significant effect on improving the toughness and bonding properties of the insulating adhesive layer.
[0020] Preferably, the added amount of the diisocyanate is 0.4 to 0.6 times the molar amount of the allyl polyoxyethylene ether. Under the above ratio, the crosslinking density is suitable.
[0021] Preferably, the temperature of the cross-linking reaction is 40-70° C. Amine catalysts may be further added to promote the cross-linking reaction, such as N,N-dimethylcyclohexylamine, N-methylmorpholine, N,N'-dimethylpyridine, and the like.
[0022] In the present invention, the epoxy resin can be selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic modified epoxy resin, and polyurethane modified epoxy resin.
[0023] In the present invention, the MQ silicone resin reinforcing agent is a polyorganosiloxane composed of a monofunctional chain segment and a tetrafunctional chain segment and having a double-layer structure. It is a commercially available chemical raw material. The present invention can further improve the heat resistance and insulation performance of the aluminum-based copper-clad laminate by adding the MQ silicone resin.
[0024] In the present invention, the curing agent is at least one of dicyandiamide, m-phenylenediamine and adipic acid dihydrazide.
[0025] In the present invention, the thermally conductive filler is at least one of aluminum oxide, aluminum nitride, zinc oxide, titanium oxide, silicon oxide, and silicon nitride.
[0026] The method for preparing the above-mentioned high heat-resistant aluminum-based copper-clad laminate comprises the following preparation steps:
[0027] The epoxy resin, silicone elastomer reinforcing agent, MQ silicone resin reinforcing agent, curing agent and thermal conductive filler are stirred and mixed evenly to obtain epoxy resin adhesive; the obtained epoxy resin adhesive is then coated on an aluminum plate, and then covered with copper foil and hot-pressed and cured to obtain a high heat-resistant aluminum-based copper-clad laminate.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The insulating adhesive layer component of the aluminum-based copper-clad laminate of the present invention uses a specific silicone elastomer and MQ silicone resin to synergistically enhance the epoxy resin, which can significantly improve its heat resistance and electrical insulation performance.
[0030] (2) The organic silicone elastomer reinforcing agent used in the present invention has good compatibility with epoxy resin and can form a good three-dimensional cross-linked network in the epoxy resin matrix, which has a significantly improved toughening effect without reducing its bonding performance. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] A high heat-resistant aluminum-based copper-clad laminate comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight:
[0034] 100 parts of E-51 epoxy resin; 8 parts of silicone elastomer reinforcing agent; 4 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 6 parts of curing agent dicyandiamide; 10 parts of thermal conductive filler aluminum oxide.
[0035] The silicone elastomer reinforcing agent is prepared by the following method:
[0036] (1) Add side chain hydrogenated polysiloxane (Dow Corning hydrogenated silicone oil, viscosity 120 cs, weight average molecular weight 7500, hydrogen content 0.60%) and allyl polyoxyethylene ether APEG-1200 into N-methylpyrrolidone and stir to dissolve evenly, the molar ratio of allyl polyoxyethylene ether to the active hydrogen content of side chain hydrogenated polysiloxane is 0.8:1, then add vinyl platinum complex catalyst, heat to 70°C under nitrogen protection, stir and react until the alkenyl reaction is complete, and obtain a polyether grafted polysiloxane solution.
[0037] (2) Toluene diisocyanate and catalyst N,N-dimethylcyclohexylamine are added to the obtained polyether grafted polysiloxane solution for cross-linking reaction, wherein the amount of toluene diisocyanate added is 0.5 times the molar amount of allyl polyoxyethylene ether, and the amount of catalyst N,N-dimethylcyclohexylamine added is 2% of the mass of hexamethylene diisocyanate. The cross-linking reaction temperature is controlled at 50°C and the reaction time is 2 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain a silicone elastomer reinforcing agent.
[0038] The preparation method of the high heat-resistant aluminum-based copper-clad laminate of this embodiment includes the following preparation steps:
[0039] The raw materials were weighed according to the above weight parts, and E-51 epoxy resin, silicone elastomer reinforcing agent, MQ silicone resin reinforcing agent, curing agent dicyandiamide and thermal conductive filler alumina were stirred and mixed to obtain epoxy resin glue; the obtained epoxy resin glue was then coated on an aluminum plate (the thickness of the glue layer was about 120 μm), and then covered with copper foil and hot-pressed and cured (temperature 180°C, surface pressure 10 kgf / cm 2 , vacuum degree below -0.95Mpa, hot pressing for 3min) to obtain a high heat-resistant aluminum-based copper-clad laminate.
[0040] The aluminum-based copper-clad laminate prepared in this embodiment was tested for peel strength (GB / T 31988-2015), heat resistance (solder immersion time, 288°C), electrical insulation performance (volume resistivity and surface resistivity) and toughness (heat shock after punching, CPCA4105-2010). The results showed that the peel strength was 1.28 N / mm, the solder immersion time was 560 s, and the volume resistivity was 4.79×10 8 MΩ·cm, surface resistivity 1.34×10 7 MΩ, no delamination or cracking due to thermal shock after punching.
[0041] The aluminum-based copper-clad laminate obtained by epoxy resin adhesive (100 parts of E-51 epoxy resin, 6 parts of dicyandiamide curing agent, and 10 parts of alumina thermal conductive filler) without adding silicone elastomer reinforcing agent and MQ silicone resin reinforcing agent was used as the control group. The performance results of the control group were as follows: peel strength 0.73N / mm, solder immersion resistance time 262s, volume resistivity 6.27×10 5 MΩ·cm, surface resistivity 3.85×10 4 MΩ, delamination occurs due to thermal shock after punching.
[0042] It can be seen from the above results that the present invention can significantly improve the bonding strength, heat resistance, insulation performance and toughness of the insulating adhesive layer by adding an organic silicone elastomer reinforcing agent and an MQ silicone resin reinforcing agent into the insulating adhesive layer.
[0043] Comparative Example 1
[0044] A high heat-resistant aluminum-based copper-clad laminate, compared with Example 1, no silicone elastomer reinforcing agent is added to the insulating adhesive layer, and an equal amount of MQ silicone resin reinforcing agent is used instead, and the rest is the same. The insulating adhesive layer is prepared from the following components in parts by weight:
[0045] 100 parts of E-51 epoxy resin; 12 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 6 parts of curing agent dicyandiamide; 10 parts of thermal conductive filler alumina.
[0046] The performance test results of the aluminum-based copper-clad laminate prepared in this comparative example showed that the peel strength was 1.07N / mm, the solder immersion time was 395s, and the volume resistivity was 2.57×10 7 MΩ·cm, surface resistivity 4.16×10 5 MΩ, obvious delamination occurs after thermal shock after punching.
[0047] By comparing the results of this comparative example with Example 1, it can be seen that the addition of MQ silicone resin can improve the bonding strength, heat resistance and insulation performance of the insulating adhesive layer to a certain extent, but the improvement effect on toughness is not significant. The present invention can effectively improve the toughness of the insulating adhesive layer on the basis of further significantly improving the bonding strength, heat resistance and insulation performance through the synergistic effect of the silicone elastomer and the MQ silicone resin.
[0048] Comparative Example 2
[0049] A high heat-resistant aluminum-based copper-clad laminate, compared with Example 1, uses an equal amount of polyether grafted polysiloxane to replace the silicone elastomer reinforcing agent, and the rest is the same, and the insulating adhesive layer is prepared from the following components in parts by weight:
[0050] 100 parts of E-51 epoxy resin; 8 parts of polyether grafted polysiloxane; 4 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 6 parts of curing agent dicyandiamide; 10 parts of thermal conductive filler alumina.
[0051] The polyether grafted polysiloxane is obtained by removing the organic solvent from the polyether grafted polysiloxane solution obtained in step (1) of Example 1 through reduced pressure distillation.
[0052] The performance test results of the aluminum-based copper-clad laminate prepared in this comparative example showed that the peel strength was 0.92N / mm, the solder immersion time was 430s, and the volume resistivity was 5.26×10 7 MΩ·cm, surface resistivity 1.10×10 6 MΩ, delamination occurs due to thermal shock after punching.
[0053] By comparing the results of this comparative example with Example 1 and Comparative Example 1, it can be seen that the present invention adopts diisocyanate to cross-link the polyether grafted polysiloxane to form an elastomeric structure, which has a very significant effect on improving the toughness and bonding properties of the insulating adhesive layer, and also plays a certain role in improving the heat resistance and insulation performance.
[0054] Example 2
[0055] A high heat-resistant aluminum-based copper-clad laminate comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight:
[0056] 100 parts of E-51 epoxy resin; 8 parts of silicone elastomer reinforcing agent; 4 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 6 parts of curing agent dicyandiamide; 10 parts of thermal conductive filler aluminum oxide.
[0057] The silicone elastomer reinforcing agent is prepared by the following method:
[0058] (1) Add side chain hydrogenated polysiloxane (Dow Corning hydrogenated silicone oil, viscosity 150 cs, weight average molecular weight 9000, hydrogen content 0.55%) and allyl polyoxyethylene ethers of different molecular weights (APEG-500, APEG-1000, APEG-2000, APEG-2400) into N-methylpyrrolidone and stir to dissolve evenly. The molar ratio of the active hydrogen content of allyl polyoxyethylene ether to the side chain hydrogenated polysiloxane is 0.85:1. Then add a vinyl platinum complex catalyst, heat to 70°C under nitrogen protection, stir and react until the olefinic reaction is complete, and obtain a polyether grafted polysiloxane solution.
[0059] (2) adding hexamethylene diisocyanate to the obtained polyether grafted polysiloxane solution for cross-linking reaction, wherein the amount of hexamethylene diisocyanate added is 0.5 times the molar amount of allyl polyoxyethylene ether, the cross-linking reaction temperature is controlled at 65°C, and the reaction time is 3 hours. After the reaction is completed, the organic solvent is removed by vacuum distillation to obtain a silicone elastomer reinforcing agent.
[0060] The preparation method of the high heat-resistant aluminum-based copper-clad laminate of this embodiment includes the following preparation steps:
[0061] The raw materials were weighed according to the above weight parts, and E-51 epoxy resin, silicone elastomer reinforcing agent, MQ silicone resin reinforcing agent, curing agent dicyandiamide and thermal conductive filler alumina were stirred and mixed to obtain epoxy resin glue; the obtained epoxy resin glue was then coated on an aluminum plate (the thickness of the glue layer was about 120 μm), and then covered with copper foil and hot-pressed and cured (temperature 180°C, surface pressure 10 kgf / cm 2 , vacuum degree below -0.95Mpa, hot pressing for 3min) to obtain a high heat-resistant aluminum-based copper-clad laminate.
[0062] The performance tests were conducted on the aluminum-based copper-clad laminates prepared with the silicone elastomer reinforcing agent obtained from allyl polyoxyethylene ether with different molecular weights in this example. The results are shown in Table 1 below.
[0063] Table 1
[0064] Test items APEG-500 APEG-1000 APEG-2000 APEG-2400 Peel strength, N / mm 1.19 1.25 1.28 1.24 Solder immersion time, s 434 522 618 487 Volume resistivity, MΩ·cm <![CDATA[2.58×10 8 ]]> <![CDATA[4.66×10 8 ]]> <![CDATA[5.03×10 8 ]]> <![CDATA[4.52×10 8 ]]> Surface resistivity, MΩ <![CDATA[0.85×10 7 ]]> <![CDATA[1.25×10 7 ]]> <![CDATA[1.47×10 7 ]]> <![CDATA[1.21×10 7 ]]> Thermal shock after punching Obvious cracking No delamination or cracking No delamination or cracking No delamination or cracking
[0065] From the results in Table 1, it can be seen that during the preparation of the silicone elastomer reinforcing agent, too low molecular weight of allyl polyoxyethylene ether will lead to a significant decrease in the heat resistance and toughness of the final aluminum-based copper-clad laminate, and its bonding performance and insulation performance will also be reduced to a certain extent. The reason may be that the low molecular weight allyl polyoxyethylene ether grafted polysiloxane has poor compatibility with the epoxy resin matrix, and its own dispersion effect on MQ silicone resin is reduced, resulting in a decrease in the improvement effect. The weight average molecular weight of allyl polyoxyethylene ether is in the range of 1000 to 2400, which can achieve good comprehensive improvement performance, and the raw material source is wide and the cost is low.
[0066] Example 3
[0067] A high heat-resistant aluminum-based copper-clad laminate comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight:
[0068] 100 parts of BPF epoxy resin; 4 parts of silicone elastomer reinforcing agent; 2 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 8 parts of curing agent m-phenylenediamine; 10 parts of thermal conductive filler aluminum oxide and 10 parts of silicon oxide.
[0069] The silicone elastomer reinforcing agent is prepared by the following method:
[0070] (1) Add side chain hydrogenated polysiloxane (Dow Corning hydrogenated silicone oil, viscosity 120 cs, weight average molecular weight 7500, hydrogen content 0.60%) and allyl polyoxyethylene ether APEG-2000 into N,N-dimethylformamide and stir to dissolve evenly. The molar ratio of allyl polyoxyethylene ether to the active hydrogen content of side chain hydrogenated polysiloxane is 0.85:1. Then add vinyl platinum complex catalyst, heat to 70°C under nitrogen protection, stir and react until the alkenyl reaction is complete, and obtain a polyether grafted polysiloxane solution.
[0071] (2) Adding diphenylmethane diisocyanate and catalyst N-methylmorpholine to the obtained polyether grafted polysiloxane solution for cross-linking reaction, the amount of diphenylmethane diisocyanate added is 0.6 times the molar amount of allyl polyoxyethylene ether, and the amount of catalyst N-methylmorpholine added is 2% of the mass of diphenylmethane diisocyanate. The cross-linking reaction temperature is controlled at 60°C and the reaction time is 2 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain a silicone elastomer reinforcing agent.
[0072] The preparation method of the high heat-resistant aluminum-based copper-clad laminate of this embodiment includes the following preparation steps:
[0073] The raw materials were weighed according to the above weight parts, and the BPF epoxy resin, the silicone elastomer reinforcing agent, the MQ silicone resin reinforcing agent, the curing agent m-phenylenediamine and the thermal conductive fillers alumina and silicon oxide were stirred and mixed to obtain epoxy resin glue; the obtained epoxy resin glue was then coated on the aluminum plate (the thickness of the glue layer was about 120 μm), and then covered with copper foil and hot-pressed and cured (temperature 180°C, surface pressure 10 kgf / cm 2 , vacuum degree below -0.95Mpa, hot pressing for 3min) to obtain a high heat-resistant aluminum-based copper-clad laminate.
[0074] The performance test results of the aluminum-based copper-clad laminate obtained in this embodiment show that the peel strength is 1.16N / mm, the solder immersion time is 524s, and the volume resistivity is 3.67×10 8 MΩ·cm, surface resistivity 1.18×10 7 MΩ, no delamination or cracking due to thermal shock after punching.
[0075] Example 4
[0076] A high heat-resistant aluminum-based copper-clad laminate comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight:
[0077] 100 parts of polyurethane modified epoxy resin; 16 parts of silicone elastomer reinforcing agent; 6 parts of MQ silicone resin reinforcing agent (DY-MQ102N methyl MQ silicone resin); 2 parts of curing agent adipic acid dihydrazide.
[0078] The silicone elastomer reinforcing agent is prepared by the following method:
[0079] (1) Add side chain hydrogenated polysiloxane (Dow Corning hydrogenated silicone oil, viscosity 80 cs, weight average molecular weight 5000, hydrogen content 0.76%) and allyl polyoxyethylene ether APEG-2000 into N-methylpyrrolidone and stir to dissolve evenly, the molar ratio of allyl polyoxyethylene ether to the active hydrogen content of side chain hydrogenated polysiloxane is 0.75:1, then add vinyl platinum complex catalyst, heat to 80°C under nitrogen protection, stir and react until the alkenyl reaction is complete, and obtain a polyether grafted polysiloxane solution.
[0080] (2) adding isophorone diisocyanate to the obtained polyether grafted polysiloxane solution for cross-linking reaction, wherein the amount of isophorone diisocyanate added is 0.4 times the molar amount of allyl polyoxyethylene ether, the cross-linking reaction temperature is controlled at 70°C, and the reaction time is 2 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain a silicone elastomer reinforcing agent.
[0081] The preparation method of the high heat-resistant aluminum-based copper-clad laminate of this embodiment includes the following preparation steps:
[0082] The raw materials were weighed according to the above weight parts, and the polyurethane modified epoxy resin, the silicone elastomer reinforcing agent, the MQ silicone resin reinforcing agent, and the curing agent adipic acid dihydrazide were stirred and mixed uniformly to obtain epoxy resin glue; the obtained epoxy resin glue was then coated on an aluminum plate (the adhesive layer thickness was about 120 μm), and then covered with copper foil and hot-pressed and cured (temperature 180°C, surface pressure 10 kgf / cm 2 , vacuum degree below -0.95Mpa, hot pressing for 3min) to obtain a high heat-resistant aluminum-based copper-clad laminate.
[0083] The performance test results of the aluminum-based copper-clad laminate obtained in this example showed that the peel strength was 1.75 N / mm, the solder immersion time was 655 s, and the volume resistivity was 6.59×10 8 MΩ·cm, surface resistivity 2.96×10 7 MΩ, no delamination or cracking due to thermal shock after punching.
[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high heat-resistant aluminum-based copper-clad laminate, characterized in that: The invention comprises a copper foil layer, an insulating adhesive layer and an aluminum plate layer which are arranged in sequence, wherein the insulating adhesive layer is prepared from the following components in parts by weight: Epoxy resin 100 parts; 4-16 parts of silicone elastomer reinforcing agent; MQ silicone resin enhancer 1~6 parts; 2~8 parts of curing agent; Thermal conductive filler 0~40 parts; The silicone elastomer reinforcing agent is prepared by the following method: (1) adding side chain hydrogen-containing polysiloxane and allyl polyoxyethylene ether to an organic solvent and stirring to dissolve them uniformly, then adding a platinum complex catalyst, heating and stirring under an inert atmosphere to react until the alkenyl reaction is complete, thereby obtaining a polyether grafted polysiloxane solution; (2) adding diisocyanate to the obtained polyether grafted polysiloxane solution to carry out a cross-linking reaction, and after the reaction is completed, removing the organic solvent by reduced pressure distillation to obtain a silicone elastomer reinforcing agent; The weight average molecular weight of the allyl polyoxyethylene ether is 1000-2400 g / mol.
2. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The side chain hydrogen-containing polysiloxane has a weight average molecular weight of 2000-15000 g / mol and an active hydrogen content of 0.2%-0.8%.
3. The high heat-resistant aluminum-based copper-clad laminate according to claim 2, characterized in that: The molar ratio of the allyl polyoxyethylene ether to the active hydrogen content in the side chain hydrogen-containing polysiloxane is 0.7-1:
1.
4. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The organic solvent in step (1) is N-methylpyrrolidone or N,N-dimethylformamide; the temperature of the heating and stirring reaction is 60-90°C.
5. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The diisocyanate in step (2) is at least one of toluene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate and isophorone diisocyanate.
6. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The amount of diisocyanate added in step (2) is 0.4-0.6 times the molar amount of allyl polyoxyethylene ether; and the temperature of the cross-linking reaction is 40-70°C.
7. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic modified epoxy resin and polyurethane modified epoxy resin.
8. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The curing agent is at least one of dicyandiamide, m-phenylenediamine and adipic acid dihydrazide.
9. The high heat-resistant aluminum-based copper-clad laminate according to claim 1, characterized in that: The thermally conductive filler is at least one of aluminum oxide, aluminum nitride, zinc oxide, titanium oxide, silicon oxide, and silicon nitride.
10. A method for preparing a high heat-resistant aluminum-based copper-clad laminate according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: The epoxy resin, silicone elastomer reinforcing agent, MQ silicone resin reinforcing agent, curing agent and thermal conductive filler are stirred and mixed evenly to obtain epoxy resin adhesive; the obtained epoxy resin adhesive is then coated on an aluminum plate, and then covered with copper foil and hot-pressed and cured to obtain a high heat-resistant aluminum-based copper-clad laminate.
Citation Information
Patent Citations
High heat-resistant and highly insulating and heat-conducting aluminum-based copper clad laminate adhesive composition and preparation process
CN102746615B
A silicone resin-based aluminum-based copper clad laminate and its preparation method
CN106467668B
Organic silicon resin aluminum-based copper-clad plate and production method thereof
CN106467668A
Waterproof reinforced composite and preparation method thereof
CN108441008A